ANALISIS DAN PERANCANGAN SISTEM INFORMASI DISTRIBUSI BIBIT SAWIT BERSUBSIDI PADA DINAS PERKEBUNAN PROVINSI JAMBI - Rezki, Lisa Purnama; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2019)
Oil palm is one of the leading plantation commodities in Jambi Province, in addition to plantationcompanies, farmers independently play an active role in participating in the development of oil palmexpansion. Requests submitted by farmers from several regencies are still on behalf of the temporaryfarmer group which is more recommended by individuals so that the people who have not received thesubsidized palm oil seeds consider that the Jambi Provincial Plantation Service does not carry out thedistribution of oil fairly and evenly. The aim of the study was to analyze and design an informationsystem for distributing subsidized palm seeds with research benefits to make it easier for the JambiProvincial Plantation Office to distribute oil palm seedlings to farmers throughout the district, encourageinterest in seed producers to use quality and certified seeds, and minimize the circulation of low qualityseeds and not certified. The solution offered is a change in the information system displayed on a websitebased basis, through which this system makes it easy for visitors to submit requests for palm oil seedsquickly and easily. The system modeling tool used is UML (Unified Modeling Language). The resultingoutput is a prototype with a report on the distribution of subsidized palm oil seedlings distribution.